Urban agriculture support policies in West Africa. Taking account of informal arrangements - Robineau, Ophélie (Perspective, 2015)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"In West Africa, urban agriculture plays an economic, environmental and social role. However, the support policies and actions that are beginning to target this activity remain relatively ineffective, since they fail to take into account informal arrangements between stakeholders — farmers, livestock holders, waste managers, and authorities —, or the spatial organisation of these activities and the proximity required between them. Supporting urban agriculture therefore calls for a global approach that takes into account these informal arrangements and this need for proximity."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"In West Africa, urban agriculture plays an economic, environmental and social role. However, the support policies and actions that are beginning to target this activity remain relatively ineffective, since they fail to take into account informal arrangements between stakeholders — farmers, livestock holders, waste managers, and authorities —, or the spatial organisation of these activities and the proximity required between them. Supporting urban agriculture therefore calls for a global approach that takes into account these informal arrangements and this need for proximity."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">In West Africa, urban agriculture plays an economic, environmental and social role. However, the support policies and actions that are beginning to target this activity remain relatively ineffective, since they fail to take into account informal arrangements between stakeholders — farmers, livestock holders, waste managers, and authorities —, or the spatial organisation of these activities and the proximity required between them. Supporting urban agriculture therefore calls for a global approach that takes into account these informal arrangements and this need for proximity.